2018
DOI: 10.22159/ajpcr.2018.v11i5.11478
|View full text |Cite
|
Sign up to set email alerts
|

A Review on Tabernaemontana spp.: Multipotential Medicinal Plant

Abstract: Plants in the genus Tabernaemontana have been using in Thai and Chinese traditional medicine for the treatment several diseases. The great majority constituents of Tabernaemontana species have already been subjected to isolation and identification of monoterpene indole alkaloids present in their several parts. Many of monoterpene indole alkaloids exhibited a wide array of several activities. The biogenesis, classification, and biological activities of these alkaloids which found in Tabernaemontana plants were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
16
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 36 publications
1
16
0
2
Order By: Relevance
“…The histochemical analysis of the laticifers and latex within the vegetative organs of T. ventricosa revealed for the first time in this species the presence of carboxylated polysaccharides ( Figure 7 a and Figure 8 a), lipophilic and hydrophilic substances ( Figure 7 b and Figure 8 b), proteins ( Figure 7 i and Figure 8 l), phenolics ( Figure 7 e and Figure 8 i), terpenoids ( Figure 7 d and Figure 8 d), neutral lipids ( Figure 7 g and Figure 8 h), alkaloids ( Figure 7 j and Figure 8 e), mucilage and pectin ( Figure 7 k and Figure 8 f), resin acids ( Figure 7 f and Figure 8 g), and acidic substances ( Figure 7 l and Figure 8 j). These findings are consistent with previous studies, as the compounds within the laticifers and latex were previously detected in species belonging to the genus Tabernaemontana and may be of therapeutic and pharmacological importance [ 42 , 43 , 44 , 45 , 46 , 47 ]. Furthermore, regarding the chemical constituents detected within leaf and stem sections of T. ventricosa , studies have shown a possible association between the secondary metabolites of latex and defense mechanisms against pathogens and herbivores [ 13 , 15 , 16 , 20 , 27 , 48 , 49 ].…”
Section: Resultssupporting
confidence: 93%
See 3 more Smart Citations
“…The histochemical analysis of the laticifers and latex within the vegetative organs of T. ventricosa revealed for the first time in this species the presence of carboxylated polysaccharides ( Figure 7 a and Figure 8 a), lipophilic and hydrophilic substances ( Figure 7 b and Figure 8 b), proteins ( Figure 7 i and Figure 8 l), phenolics ( Figure 7 e and Figure 8 i), terpenoids ( Figure 7 d and Figure 8 d), neutral lipids ( Figure 7 g and Figure 8 h), alkaloids ( Figure 7 j and Figure 8 e), mucilage and pectin ( Figure 7 k and Figure 8 f), resin acids ( Figure 7 f and Figure 8 g), and acidic substances ( Figure 7 l and Figure 8 j). These findings are consistent with previous studies, as the compounds within the laticifers and latex were previously detected in species belonging to the genus Tabernaemontana and may be of therapeutic and pharmacological importance [ 42 , 43 , 44 , 45 , 46 , 47 ]. Furthermore, regarding the chemical constituents detected within leaf and stem sections of T. ventricosa , studies have shown a possible association between the secondary metabolites of latex and defense mechanisms against pathogens and herbivores [ 13 , 15 , 16 , 20 , 27 , 48 , 49 ].…”
Section: Resultssupporting
confidence: 93%
“…Moreover, previous reports on Tabernaemontana species showed that the alkaloids dregamine and voacangine isolated from T. elegans and indole alkaloids found in T. catharinensis exhibited substantial anti-bacterial activity and have medicinal value [ 47 , 50 ]. It has been observed that plants within the genus Tabernaemontana often obtain a profusely high alkaloid content, usually displaying biological activity [ 42 , 45 ]. According to Van Beek et al (1984), alkaloids are organic nitrogenous compounds with the nitrogen being either in its primary, secondary, or tertiary form [ 43 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Since L. acida is used in combination with other plant species in various herbal concoctions, it is important to evaluate the synergistic effects of the different extracts and their ability to enhance the efficiency of the additive mixtures. Detailed phytochemical, pharmacological, and toxicological studies will enable researchers to evaluate the therapeutical importance of the species in tropical Africa [83,84].…”
Section: Resultsmentioning
confidence: 99%